Evaluation of Password Security Compliance Using Nist SP 800-63 - Mohammad Ghifari Yusuf; Jarot Sembodo Suroso (Syntax Idea)
This study aims to investigate password compliance within a web application used by 174 users, following NIST SP 800-63 guidelines. A questionnaire was employed to assess user password attributes aligned with NIST guidelines, using a binary scoring system for compliance. The research findings will unveil strengths and weaknesses in password policies and their implementation within the web application. As a result, the security compliance level of the web application is approximately 28.30%. Based on these findings, recommendations will be provided to enhance the web application’s security